Attainment of Course Outcomes (COs) and Program Outcomes (POs) in Outcome Based Education (OBE) - Thangaraj, K.; Anbumalar, S.; Jamuna, P.; Janagiraman, A. (Journal of Engineering Education Transformations, 2025)
Quality assurance and upgrading processes play a pivotal role in checking whether te set educational objectives meet a typical quality in education. To guarantee this, the National Board of Accreditation (NBA) has instituted a novel Outcome Based Education system. As per the criteria established by the NBA, a fundamental requirement is the evaluation of Course Outcomes (COs), Program Outcomes (POs), and Program Specific Outcomes (PSOs). It assesses the expertise, knowledge, and attitudes that students acquire through the program. Achieving Program Outcomes is possible through the successful completion of Course Outcomes associated with that particular program. It helps to improve students’ technical skills, knowledge, and attitudes. This paper presents an approach for assessing the achievement of both course and program outcomes. It also provides recommended target values to measure the degree of intended growth in students after a teaching and learning process.